Participative plant improvement as a tool for selection of tomato cultivars (Solanum lycopersicon L.) - Lambert G., Tania; Rodríguez L., Luis; Rivero H., Marisol; Castro C., Bárbara (Revista de Ciencias Agrícolas, 2013)
With the objective to contribute to the development and diversification of cultivars of tomato crop at San Apapucio community (Cuba), three experiments were developed on a Fluvisol soil. The agromorphological behavior of seven varieties of tomato in seedbed, plantation and in a biodiversity exhibition was evaluated as mechanisms to stimulate the introduction of new varieties, during the winter campaign, December/2010 to April/2011. The experiment was performed by using a completely randomized design, with varieties as the treatments and locality as an additional factor. Height of plant and number of leaves showed the best result in seedbed; the best agromorphological behavior in plantation was reached by Lignon in plant height; Mariela in diameter of stalk,number of fruits per plant and commercial yield, and Mayle in average weight. The effects in the biodiversity exhibition were favorable, because 93% of varieties and lines were selected at least by one participant; the most selected variety was Mariela that was preferred by its yield and fruit size. It is showed the advantage of using combined experiments of varieties with results of the biodiversity exhibition to select, adopt and introduce new varieties of tomato for producción.